An integrated assessment of technological pathways and socioeconomic impacts for sustainable power system transition in Indonesia - Widodo Wahyu Purwanto; Djoni Hartono; Akhmad Herman Yunowo; Heri Hermansyah; Nadhilah Reyseliani; Ahmad Syauqi; Rosa Citra Aprilia (Advances in Climate Change Research)
The energy transition has unique and profound socioeconomic impacts for the developing and coal-producing countries, due to the distinctive country's characteristics. The overall development context and challenges comprising technological pathways, investment, value added, employment and inequality must be considered. For the case of Indonesia, as one of the world's largest coal-producing, the archipelagic nature with various island topography, sociocultural diversity as well as very high population really needs a comprehensive energy transition research considering the above aspects, which is so far still lacking. Therefore, this current study presents an integrated assessment of technological change and socioeconomics impact for power transition pathways in Indonesia using the Integrated MARKAL-EFOM System (TIMES) and their socioeconomics implications using the Miyazawa Input–Output Model (MIOM). Four scenarios were applied namely business-as-usual (BAU), 100% renewable energy (100%RE), Paris Agreement 1.5 °C without coal phase-out (PA1.5), and that of with coal phase-out (PA1.5PO). The results show that by 2060, 100%RE without applying carbon capture and storage (CCS) creates an extreme power flexibility which requires ample energy storage but does not attain net-zero. To meet the 1.5 °C carbon budget, PA1.5 and PA1.5PO require substantial renewable energy deployment, particularly in utility-scale solar PV, energy storage, and low-carbon technologies. These two scenarios exhibit a notable increase in total installed capacity, ranging 3.37–3.83 times higher than the BAU scenario. PA1.5PO, plays an increasing role natural gas as bridge fuel in advanced gas power from 2035 to its peak in 2050. PA scenarios require a higher installed capacity compared to BAU, corresponding to a substantial total investment cost of almost 2.5 times in 2060. The MIOM results show that these scenarios have a stronger impact on household income and employment compared to BAU. However, the impact on value added (VA) only surpasses BAU until 2045, specifically in the PA1.5PO scenario. In the long term, PA1.5PO generates the highest value added and household income, whereas 100%RE scenario has the highest employment and the highest value added in the electricity sector. In contrast, non-energy sectors related to conventional energy supply chains may face challenges. However, PA1.5PO can better mitigate adverse effects. The key findings could provide an insight for policymakers better understand transition pathway and its socioeconomic impacts to ensure a fair transition towards a carbon-neutral economy.